Penelope: a study in the manipulation of myth - Gilchrist, K (1997)
Mythological figures play a number of roles in literature: they may, of course, appear in person as developed characters, but they may also contribute more indirectly, as part of the substratum from which rhetorical argument or literary characterisation are constructed, or as a background against which other literary strategies (for example, the rewriting of epic or the appropriation of Greek culture by the Romans) can be marked out. This thesis sets out to examine the way in which the figure of Penelope emerges from unknown origins, acquires portrayal in almost canonical form in Homer's Odyssey, and then takes part in the subsequent interplay of Homeric and other literary allusions throughout later Classical literature (with chapters focusing particularly on fifth-century Greek tragedy, Hellenistic poetry, and Augustan poetry). In particular, it focuses on the manner in which, despite the potential complexities of the character and the possible variants in her story, she became quintessentially a stereotypical figure. In addition to considering example where Penelope is evoked by name, a case is also made for the thesis that allusion, or intertextual reference, could also evoke Penelope for an ancient audience. A central point of discussion is what perception of Penelope would be called to mind by intertextual reference. The importance of approaching relationships between ancient texts in intertextual terms rather terms of strict "allusion" is thus demonstrated. The formation of the simplified picture is considered in the light of folk-tale motifs, rhetorical simplification of myth, and favoured story patterns. The appendices include a summary of the myth of Penelope with all attested variants, and a comprehensive list of explicit references to her in classical literature.